Portraying the Implementation of Religious Moderation in Non-Religious Universities in West Java - Didin Wahidin; Nandang Arif Saefuloh; Zubaedah Wiji Lestari (Yayasan Keluarga Guru Mandiri, 2023)
Since its independence, Indonesia has had to overcome numerous difficulties. Terrorism, radicalism, intolerance, and separatism (TRIS), which endangers Indonesia's unity, are one of the problems. According to numerous studies, many colleges are affected by the threats of terrorism, radicalism, intolerance, and separatism. This study aims to portray how religious moderation is implemented in non-religious universities in West Java. The implementation of religious moderation is seen from six indicators: understanding the concept, university policies about religious moderation, national commitment, tolerance, anti-violence attitudes, the accommodation of local wisdom, and compliance with laws and regulations. A mixed-method approach was used in this study, which was conducted at ten universities in West Java. Observation, interviews, documentation, and questionnaires were used to obtain the data. University leaders, lecturers, and students served as the data sources. The study concludes that non-religious universities in West Java have a good and enough carrying capacity and anticipatory readiness to stop the expansion of TRIS by enforcing religious moderation. However, to have a powerful deterrent against the rise of terrorism, radicalism, intolerance, and separatism, it is vital to deepen and affirm the commitment to religious moderation.